Analysis of Drug Inventory Control Using the ABC Method of Critical Index in Islamic Hospital Ibnu Sina Padang in 2021 for Public Welfare - Putri Widya Herman; Husna Yetti; Isniati Isniati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Hospitals have a very strategic role in an effort to accelerate the improvement of the health status of the Indonesian people. So, the service system must always be reviewed to anticipate competition. The level of efficiency in the use of funds for drug procurement depends on the ability to manage it. Selection of the right method can help achieve good and appropriate drug management. It is known that the Medicines Formulary of the Islamic Hospital of Ibnu Sina Padang has not been updated regularly, pharmacy installations have not implemented more in-depth inventory control methods, and are still experiencing drug shortages. The purpose of this study was to analyze the implementation of drug control using the ABC critical index analysis method at the Islamic Hospital Ibnu Sina Padang in 2021. The research method is quantitative in the form of operational research. The results of this study are group A ABC critical index analysis consists of 9 drug items (18.75%) with an investment value of 14.19% of the total investment value and the number of uses is 54.87% of the total drug use, group B consists of of 34 drug items (70.83%) with an investment value of 80.25% of the total investment value and the number of known uses is 44.87% of the total drug use, group C consists of 5 drug items (10.42%) with an investment value 5.56% of the total investment value and 0.26% of the total use of drugs. It is hoped that the results of this study can be used as input and consideration in managing drug supplies in hospitals. The results of this study are group A ABC critical index analysis consists of 9 drug items (18.75%) with an investment value of 14.19% of the total investment value and the number of uses is 54.87% of the total drug use, group B consists of of 34 drug items (70.83%) with an investment value of 80.25% of the total investment value and the number of known uses is 44.87% of the total drug use, group C consists of 5 drug items (10.42%) with an investment value 5.56% of the total investment value and 0.26% of the total use of drugs. It is hoped that the results of this study can be used as input and consideration in managing drug supplies in hospitals.